Modeling and mitigation of bundle end power peaking in pressure tube heavy water reactor advanced fuels using thorium dioxide. (October 2018) - Dugal, C.; Colton, A.; Golesorkhi, S.; Bromley, B.P.
Graphical abstract: Highlights: Bundle end power peaking becomes more significant in advanced reactor fuels. End pellets can be downblended with thorium dioxide to reduce end power peaking. Using downblended end pellets causes fresh fuel reactivity to be slightly reduced. Abstract: Fuel bundle end power peaking in pressure tube heavy water reactors (PT-HWRs), particularly considering advanced reactor fuels (such as thorium-based fuels), was evaluated and a mitigation method was assessed. For bundles containing all the same fuel pellets, power is greatest at the bundle ends due to higher thermal neutron flux there. A method to achieve a flatter axial power profile along a bundle by downblending the fissile content in the end pellets with thorium dioxide was evaluated. The method was shown to be effective, and only a slight reduction in fresh fuel reactivity was observed.